2006
DOI: 10.2353/ajpath.2006.060180
|View full text |Cite
|
Sign up to set email alerts
|

B and T Lymphocytes Are the Primary Sources of RANKL in the Bone Resorptive Lesion of Periodontal Disease

Abstract: Receptor activator of nuclear factor-B (RANKL)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
490
0
25

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 466 publications
(537 citation statements)
references
References 57 publications
22
490
0
25
Order By: Relevance
“…Recently, it has been shown that most CD20 + B cells in periodontitis lesions express RANKL (61). However, it is unclear whether those cells are plasma cells or memory B cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that most CD20 + B cells in periodontitis lesions express RANKL (61). However, it is unclear whether those cells are plasma cells or memory B cells.…”
Section: Discussionmentioning
confidence: 99%
“…51) or are predominantly pathogenic/destructive (52,53). Activated T cells express receptor activator of NF-B ligand (RANKL), which stimulates osteoclast differentiation and bone resorption, and elevated numbers of receptor activator of NF-B ligand-expressing T cells are present in chronic human periodontitis tissue (54). However, given that T cells are heterogeneous, their net effect likely reflects the predominant induction of either a pro-(Th1 and Th17) vs anti-inflammatory (Th2 and T regulatory) phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…This may reflect the nature of the respective diseases, in which these cells are involved. To this extent, RANKL in periapical lesions has been particularly associated with fibroblastic cells, rather than T-cells [25], as opposed to periodontitis, where cells of the immune system are considered a major source of RANKL [9,26,27]. When the relative RANKL/OPG ratio was calculated, this was significantly increased in DP cells, compared to PDL cells, indicating a higher capacity for inducing bone resorption by the former cells.…”
Section: P O R P H Y R O Mo N a S G I N G I V A L I S Have Been Stumentioning
confidence: 99%